2015
DOI: 10.5901/mjss.2015.v4n1p97
|View full text |Cite
|
Sign up to set email alerts
|

Academic Advising Problems at Al-Quds University as Perceived by Students, and Its Relationship with Student’s Academic Performance

Abstract: This current study explores the main academic advising problems at Al-Quds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…This finding was consistent with the result of Hsu and Bailey (2011). In contrast, Young-Jones et al (2013) and Banat (2015) found that gender demonstrated a difference, statistically, in academic advising service students' satisfaction. Female students indicate a higher mean value of 4.053 compared to male students, even if the number of male students is higher than female students.…”
Section: Significant Difference In Students' Satisfaction Across the Various Demographic Variablesmentioning
confidence: 81%
“…This finding was consistent with the result of Hsu and Bailey (2011). In contrast, Young-Jones et al (2013) and Banat (2015) found that gender demonstrated a difference, statistically, in academic advising service students' satisfaction. Female students indicate a higher mean value of 4.053 compared to male students, even if the number of male students is higher than female students.…”
Section: Significant Difference In Students' Satisfaction Across the Various Demographic Variablesmentioning
confidence: 81%
“…According to Nguyen et al (2008), academic advising models vary considerably, and little thought is given to the efficiency and adequacy of these models. They introduced a robust academic advising framework that focused on combining technology-enhanced learning theories into a pedagogy-driven and service-oriented architecture (Banat, 2015).…”
Section: Literature Review Academic Advicementioning
confidence: 99%
“…An interesting study by Banat (2015) highlights advising-related issues at Al-Quds University, as seen by students, and its consequences on students' academic success. Three hundred and sixty-nine fulltime college students at Al-Quds University were surveyed.…”
Section: Literature Review Academic Advicementioning
confidence: 99%
“…(15) (16) The questionnaire used was in the Arabic language, and its validity and reliability was confirmed through a previous study held in Al-Quds University and using exploratory factor analysis; the factor loading for all items exceeded 0.55 (0.59 to 0.78), and the Cronbach's Alpha and Guttman split-half coefficients were 0.81 and 0.80, respectively. (17) The EI score for each individual was calculated by adding the score obtained from each answer in the questionnaire and dividing by 33, giving a summary value with minimum of 1 and maximum of 5. Based on this score, the respondents were ranked into three categories (low EI, moderate EI, high EI), shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this score, the respondents were ranked into three categories (low EI, moderate EI, high EI), shown in Table 2. (17) Students were additionally categorized into levels defined according to their academic year:…”
Section: Methodsmentioning
confidence: 99%